Pengaruh Return On Equity (ROE), Debt To Equity Ratio (DER), dan Inflasi Terhadap Return Saham Perusahaan Sektor Keuangan di Bursa Efek Indonesia Periode 2019-2023 - Jhellysia Andriani; Trisnadi Wijaya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This research aims to analyze the influence of Return on Equity (ROE), Debt to Equity Ratio (DER), and inflation on stock returns of financial sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period. The research method uses a quantitative approach with secondary data from financial reports and inflation data, and is analyzed using multiple linear regression on 59 companies with a total of 295 observations. The research results show that ROE has a positive and significant effect on stock returns, while DER and inflation have a negative but not significant effect, with a model explanation ability of 7.3% and a significant simultaneous effect on stock returns. These findings indicate that profitability is the main factor that investors pay attention to in assessing the performance of financial sector stocks, while capital structure and inflation have not been proven to play a significant role in the research period.